(untitled) - Luntz, Maurice H. (Singapore, 1994)
This book is essentially a text on the surgical management of glaucoma. It is the only book presently available that comprehensively covers all aspects of surgical management—namely, an appropriate decision-making process for introducing surgery into the management of glaucoma, a choice of the most suitable surgical procedure in individual cases of glaucoma, the preoperative preparation, anesthesia, surgical technique and postoperative care. The most effective and widely used operations are described in step-by-step detail, with excellent photographs and line drawings to illustrate the descriptions.
Keywords: Glaucoma,Glaucoma; Surgery,Atlases,Phẩu thuật,Đốt sống cổ